Efficacy of pre and post AI administration of sterile Ceftriaxone sodium on conception rate in normal and repeat breeding crossbred cattle - MAHTO, DINESH; SINGH, M P; SINGH, BALRAJ; SINHA, M P (The Indian Journal of Animal Reproduction, 2023)
A total of77 normal and repeat breeder crossbred cows were treated with single dose sterile Ceftriaxone sodium. TheCeftriaxone sodium were infused intra-uterine 8-12 hr either pre or post-insemination during same estrus to evaluate the efficacyof the medicine on the conception rate of apparently normal and repeat breeding cows. In normal animals the conception rate percentages with pre & post A.I. Ceftriaxone sodium treatment were 53.84 and 57. I 4 as compared to 33.33 and 33.33%,respectively for control group. Similarly in repeat breeding cows, the conception rates were 50 and 50.14% with pre and post AI treatment as compared to 16.66 and 16.33%, respectively for control group. The differences were highly significant (P < 0.0 I).
Keywords: Repeat breeding; conception rate; antibiotic infusion; artificial insemination